Matej Sovič in ohranjeni rokopis njegovega latinskega prevoda slovnice Meletija Smotrickega (1619) iz leta 1773 v rokopisni zbirki NUK Ljubljana - Babič, Vanda (Slavistična revija, 2008)
The author surveys a part of Zois's papers in the Manuscript section of the National and University Library in Ljubljana, i.e., three interrelated manuscripts: Sović's Latin translation of Meletij Smotrickij's Grammatiki Slavenskija pravilnoe Sintagma (1619) of 1773 and two fascicles of Sović's correspondence with the Italian Alberto Fortis. In the first, most important, manuscript - the Latin translation and taranscription of the Old Church Slavic text - the author finds a connection with the first edition of the Old Church Slavic grammar of 1619 or, rather, with the revised Moscow version of the grammar from 1684.
Keywords: 17./18.st.; korespondenca; prevodi; slovnice; Smotric'kyj, Meletij Gerasimovič; Sović, Matej; stara cerkvena slovanščina; transkripcija